Harmonics reduction of a five-level inverter by unbalanced carriers and over-modulation techniques - Fawzi Mohammed, Mustafa; Husain Ahmad, Ali; Thiab Humod, AbdulRahim (International Journal of Engineering and Technology, 2018)
The most concerns in the inverter's design are about, how to make the output voltage of the inverter sinusoidal at the desired fundamental frequency with low total harmonic distortion (THD). This paper presents a design and implementation of single-phase five-level inverter which is powered by single dc source and based on T-type multi-level inverters construction. The proposed inverter is built mainly by six IGBTs and two diodes. The used modulation technique is based on using two triangular carriers at 2000 Hz frequency and shifted by phase opposition disposition (POD) method. The carriers are made slightly unbalanced with their amplitudes. The over-modulation method is also introduced in the design to get the lowest possible THD effect without using filters. The inverter is simulated by MATLAB SIMULINK, implemented practically, and tested with the help of LabVIEW software.Â Â